2004
DOI: 10.1101/gad.1217204
|View full text |Cite
|
Sign up to set email alerts
|

Rapid accumulation of mutations during seed-to-seed propagation of mismatch-repair-defective Arabidopsis

Abstract: During the many cell divisions that precede formation of plant gametes, their apical-meristem and floral antecedents are continually exposed to endogenous and environmental mutagenic threats. Although some deleterious recessive mutations may be eliminated during growth of haploid gametophytes and functionally haploid early embryos ("haplosufficiency quality-checking"), the multiplicity of plant genome-maintenance systems suggests aggressive quality control during prior diploid growth. To test in Arabidopsis a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 21 publications
6
85
0
1
Order By: Relevance
“…As a result, Frumkin et al (37) needed more markers, as well as mismatch repair-deficient cell lines and plant strains, to detect sufficient somatic diversity. The MSH2-deficient strain of Arabidopsis used by them accumulates mutations throughout the genome and becomes morphologically abnormal (38), making it a somewhat less suitable model of normal development.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Frumkin et al (37) needed more markers, as well as mismatch repair-deficient cell lines and plant strains, to detect sufficient somatic diversity. The MSH2-deficient strain of Arabidopsis used by them accumulates mutations throughout the genome and becomes morphologically abnormal (38), making it a somewhat less suitable model of normal development.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, g = 10, the count of identified homozygous mutations is then 10m + 8t/2, which is lower than the expected count of accumulated homozygous mutations, i.e., 10 3 (m + t/2). Although we acknowledge an underestimation of the mutation rate, current knowledge does not permit us to accurately correct it, because the values of m and t are hard to estimate during plant development (Hoffman et al 2004;Ossowski et al 2010). Nevertheless, this underestimation has a limited effect on our results and conclusions because, even in the worst-case scenario, if all mutations originated after the specialization of the reproductive tissues and none originated before the specialization of the reproductive tissues, our current estimation (8t/2) would be 8/10 times the number of true accumulated mutations (10t/2), thus causing a 20% underestimation of the real mutation rate.…”
Section: Calculation Of Mutation Ratementioning
confidence: 99%
“…Taking the average mutation rate of saline transition mutations as an example, n = 42 mutations/9 lines, and g = 10, the mutation rate m = 4.67/10 = 0.467. However, this calculation may be an underestimation of the real mutation rate due to the limited number of generations (Hoffman et al 2004;Ossowski et al 2010), for the following reasons. All new mutations are heterozygous when they arise, and one quarter of the heterozygous mutations present in the germ line before the specialization of the reproductive tissues are expected to be inherited in the homozygous state at the beginning of the next generation (Hoffman et al 2004;Ossowski et al 2010).…”
Section: Calculation Of Mutation Ratementioning
confidence: 99%
“…Therefore, we decided to determine the rate of replication errors in MMR-null plants. MSH2 (MutS protein homolog 2) is an essential MMR component, and previous work with msh2 mutants demonstrated that these plants have a strong mutator phenotype (34).…”
Section: Formation Of De Novo Mutations In Mismatch Repair-deficientmentioning
confidence: 99%